Circular RNA circIGF1R controls cardiac fibroblast proliferation through regulation of carbohydrate metabolism - Arne Schmidt; Kevin Schmidt; Sonja Groß; Dongchao Lu; Ke Xiao; Dimyana Neufeldt; Sarah Cushman; Nele Lehmann; Sabrina Thum; Angelika Pfanne; Annette Just; Andreas Pich; et al. (Scientific Reports)
Abstract Excessive fibroblast proliferation and metabolic reprogramming are hallmarks of pathological cardiac remodeling, contributing significantly to impaired cardiac function. This study investigates the role of circular RNAs (circRNAs) in fibroblast metabolic reprogramming, an unexplored area with potential therapeutic implications. Through deep circRNA sequencing of cardiac tissue from heart failure (HF) patients and healthy individuals, we identified circIGF1R (hsa_circ_0005035), which exhibited dysregulation specifically in isolated cardiac fibroblasts derived from failing hearts. Silencing circIGF1R in patient-derived human cardiac fibroblasts (HCFs) led to accelerated proliferation, enhanced glycolytic activity, altered glucose trafficking, and increased glucose import. Conversely, administering recombinant circIGF1R inhibited the accelerated proliferation and enhanced glycolytic activity observed in HCFs from HF patients. Mechanistically, RNA pulldown assays and in silico analyses identified AZGP1 as a potential interaction partner facilitating the glycolysis-inhibitory and anti-proliferative functions of circIGF1R. Our findings identify circIGF1R as a pivotal regulator of fibroblast proliferation via metabolic reprogramming, particularly by glycolysis inhibition. Overexpression of circIGF1R demonstrated significant anti-fibrotic effects in cardiac fibroblasts derived from heart failure patients. These results underscore the therapeutic potential of circIGF1R in attenuating cardiac fibrosis by directly targeting fibroblast metabolism in the context of pathological cardiac remodeling.